SUBCUTANEOUS ADIPOSE TISSUE IN FEMALE PATIENTS WITH IRON DEFICIENCY ANEMIA AND OBESE WOMEN DOES NOT DIFFER IN THE EXPRESSION OF IKBΑ* - V.M. Nedoborenko; O.А. Shlykova; O.V. Izmailova; K.E. Ishcheikin; I.P. Kaidashev (Проблеми екології та медицини)
Prerequisites and objective: Abdominal obesity is a common metabolic disease characterized by excessive accumulation of white adipose tissue, with excessive production of inflammatory mediators that activate transcriptional nuclear factors, in particular the nuclear factor kB. Hepcidin is the main hormone in the systemic regulation of iron. Its expression increases with elevated level of pro-inflammatory cytokines, as a result of which the concentration of iron in the blood plasma decreases, which reliably results in the activation of NF-kB. Therefore, the aim of the research was to determine the level of expression of ІКβα in subcutaneous adipose tissue in iron deficiency anemia concurrent with obesity. Methods: The study included 40 female women. Hemogram parameters, parameters of iron metabolism (serum iron, ferritin, hepcidin, total iron binding ability of serum, saturation of transferrin by iron) in serum and level of expression of the IkBα gene in subcutaneous adipose tissue were evaluated. Research results. The examined women had an average age of 40.3 ± 7.59 years. In the distribution of patients due to the cause and degree of severity of IDA, there was no reliable difference between the groups. The control group consisted of 10 obese women without IDA. Expression of IkBα by subcutaneous adipose tissue in female patients with IDA with and without obesity compared with the control group did not display a significant difference between the groups (p <0.05). In the course of correlation analysis, the expression of IkBα by subcutaneous adipose tissue to BMI, iron and hemogram rates did not have a correlated significance. Conclusion. Subcutaneous adipose tissue in women with iron deficiency anemia with and without obesity compared with obese women has no difference in expression of IkBα.